Hubungan Kualitas Pelayanan dengan Kepuasan Pelanggan di Perusahaan X di Yogyakarta - Siti Asmaul Husna; Indra Wahyudi; Eni Rohyati (Jurnal Psikologi, 2020)
Quality of service to customers is very important as one of the business strategies. The service is expected to be able to serve the needs and desires of customers, and be able to become a benchmark to improve customer satisfaction to the company. Customer satisfaction will be the benefit of the company, creating customer loyalty.The research objectives of this research is to find out empirically about whether there is a relationship between service quality and customer satisfaction at Company X di Yogyakarta. This research uses quantitative research methods by collecting data using scale. Subjects in this research is the costumers of Company X di Yogyakarta. The data analysis technique used is the Product Moment correlation technique.Results showed that the correlation coefficient rxy = 0.312 with p= 0.006 (p <0.01). This means that there is a significant positive relationship between service quality and customer satisfaction with costumers of Company X di Yogyakarta. Conclusion of this research is that the relationship between service quality and customer satisfaction is proven to have a significant relationship